A Review on the Detection of Skull by Forensic Analysis - J.Tracy Tina Angelina; Bathula Murali Krishna; A.R.Revathi; S.R.Preethi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Skull identification is extremely important in today’s society, especially in medico-legal circumstances. As aresult, all technological advancements in this field can contribute to the growing need for precise and robusttools that allow for the establishment and verification of human identity. Identification of skulls when all otherproof and evidence are destroyed or limited requires the usage of facial reconstruction for the forensic team.The facial graphics serve as an emphasis for public attention to specifics of the case to generate additionalinvestigative guidance. The physical appearance of the face is at its best a significant cause for the purposefulidentification and communication to the investigating authorities of knowledge. Human identification is oneof the most remarkable approaches in the field of forensic medicine. The identification mission is performedin the field of forensic anthropology by the examination of the skeletal remains. Anthropologists have beenpaying attention to improve the techniques that allow accurate and clearer identification. Therefore, forensicidentification has become an active field of study and skull detection has emerged as a vital source foridentification. Skull identification is attracted and applied in many forensic areas. This review articleis asummation of the various facial reconstruction approaches and their role in forensic science to identify theindividual.